Distributive Effects of Regional Trade Agreements on the "Small Trading Partners": Mercosur and the case of Uruguay and Paraguay - Fernando Borraz; Máximo Rossi; Daniel Ferrés (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
Although trade integration has potential benefits for developing countries, it is disputed whether trade liberalization processes are, per se, sufficient for poverty reduction and inequality abatement. Abundant work has analyzed the link between tariff reduction, poverty levels and inequality in both developed and developing countries. Gains from trade are generally observed. Still, those benefits from integration are generally unevenly distributed.In our analysis we explore how gains from trade have been distributed in the two minor trade partners of MERCOSUR: Uruguay and Paraguay. We study the link between trade, poverty and inequality by analyzing the impact of trade liberalization through two main transmission channels: prices and income. Our papers show that in the case of Mercosur, the effect of trade on poverty (and income inequality) varies per country and per region. In particular, we conclude that trade integration policies cannot be regarded as a poverty-alleviating policy, per se.
Keywords: F14; F16; D30; Q17; 330; regional trade agreements; poverty; inequality